The official guide for GMAT review (Hoboken, N.J., 2012)
Reviews test-taking strategies, math and English skills, and reasoning, and provides sample tests with answers.
Keywords: Graduate Management Admission Test,Graduate Management Admission Test; Hướng dẫn học,Study guides